A flexible microbial co-culture platform for simultaneous utilization of methane and carbon dioxide from gas feedstocks. (March 2017) - Hill, Eric A.; Chrisler, William B.; Beliaev, Alex S.; Bernstein, Hans C.
Highlights: A co-cultivation technology that converts, CH4 and CO2, into microbial biomass. Robust bacterial growth on biogas and natural gas feedstocks. Continuous co-cultivation without air or O2 feed to support CH4 oxidation. A flexible co-culture technology constructed from genetically tractable bacteria. Abstract: A new co-cultivation technology is presented that converts greenhouse gasses, CH4 and CO2, into microbial biomass. The methanotrophic bacterium, Methylomicrobium alcaliphilum 20z, was coupled to a cyanobacterium, Synechococcus PCC 7002 via oxygenic photosynthesis. The system exhibited robust growth on diverse gas mixtures ranging from biogas to those representative of a natural gas feedstock. A continuous processes was developed on a synthetic natural gas feed that achieved steady-state by imposing coupled light and O2 limitations on the cyanobacterium and methanotroph, respectively. Continuous co-cultivation resulted in an O2 depleted reactor and does not require CH4 /O2 mixtures to be fed into the system, thereby enhancing process safety considerations over traditional methanotroph mono-culture platforms. This co-culture technology is scalable with respect to its ability to utilize different gas streams and its biological components constructed from model bacteria that can be metabolically customized to produce a range of biofuels and bioproducts.